2021
DOI: 10.7759/cureus.17481
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Closure of Clinically Silent Patent Ductus Arteriosus Using the Amplatzer Duct Occluder II-Additional Size: A Single-Center Experience

Abstract: Transcatheter closure is the treatment of choice for most patent ductus arteriosus (PDA) in infants, children, and adults. However, there is a controversy regarding transcatheter closure of clinically silent PDAs. Some authors favor device closure to eliminate the lifelong risk of infective endarteritis while others recommend avoiding PDA closure in such patients. The study describes our experience of closing the silent PDAs using the Amplatzer duct occluder II-additional size (ADO II-AS) (St. Jude Medical Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To avoid radiation and contrast agents the single femoral artery approach under TTE guidance was applied to transcatheter device ADO II closure of PDA in recent literatures [16][17] .For the arterial access, ADO II occluder was not only a problem of vascular complications, but also unsuitable for PDA patients with diameter lager than 5.5 mm [18] .Besides, single TTE guidance also has inherent drawbacks compared with uoroscopic guidance, such as a smaller image interface and limited operating view [19] .To our knowledge, few literatures were reported for transcatheter closure of patent ductus arteriosus from single venous approach under echocardiographic without angiography.We are the rst to systematically report the single venous approach and to provide a detailed analysis.In this study,60 cases in Group 1 were reported by single venous approach under echocardiographic without Angiography with satisfying feasibility and safety.The single venous approach under echocardiographic without angiography successfully avoided the vascular complications and reduced the damage caused by contrast agents and X-rays..It is especially suitable for patients with contrast allergy and infants. The single venous approach in Group 1 greatly reduced operation time and contrast volume compared with the control group in Group 2.The reduction in operative time and contrast volume usage re ected the reduction in radiation dose, which was bene cial to both patients and doctors [20].Of course, the reliability of TTE measurements is critical for proper device size.In Paudel's study [21],TTE measurements are comparable to angiographic measurements, thereby assisting in appropriate device size selection.In Group 2, the shape, position and size of PDA were evaluated by preoperative echocardiography instead of descending aortography and the position of the occluder was determined by the aortography and echocardiography performed before releasing the device,making the entire procedure easier and less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid radiation and contrast agents the single femoral artery approach under TTE guidance was applied to transcatheter device ADO II closure of PDA in recent literatures [16][17] .For the arterial access, ADO II occluder was not only a problem of vascular complications, but also unsuitable for PDA patients with diameter lager than 5.5 mm [18] .Besides, single TTE guidance also has inherent drawbacks compared with uoroscopic guidance, such as a smaller image interface and limited operating view [19] .To our knowledge, few literatures were reported for transcatheter closure of patent ductus arteriosus from single venous approach under echocardiographic without angiography.We are the rst to systematically report the single venous approach and to provide a detailed analysis.In this study,60 cases in Group 1 were reported by single venous approach under echocardiographic without Angiography with satisfying feasibility and safety.The single venous approach under echocardiographic without angiography successfully avoided the vascular complications and reduced the damage caused by contrast agents and X-rays..It is especially suitable for patients with contrast allergy and infants. The single venous approach in Group 1 greatly reduced operation time and contrast volume compared with the control group in Group 2.The reduction in operative time and contrast volume usage re ected the reduction in radiation dose, which was bene cial to both patients and doctors [20].Of course, the reliability of TTE measurements is critical for proper device size.In Paudel's study [21],TTE measurements are comparable to angiographic measurements, thereby assisting in appropriate device size selection.In Group 2, the shape, position and size of PDA were evaluated by preoperative echocardiography instead of descending aortography and the position of the occluder was determined by the aortography and echocardiography performed before releasing the device,making the entire procedure easier and less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with small or tiny PDAs were selected for transcatheter closure via an arterial route after a detailed assessment at the outpatient clinic. The authors demonstrated in another study [11] that hemodynamic catheterization assessment might not be required in clinically silent PDAs. As a result, transcatheter closure of the small/tiny PDA without hemodynamic evaluation may significantly reduce the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…United States Food and Drug Administration (FDA) approval of the Amplatzer Piccolo Occluder for use in premature infants ≥700 g was obtained on January 11, 2019 (2). ADO-II AS has been used with high procedural success in transcatheter PDA closure in larger, small babies, and premature infants in many centers in the United States and Europe (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). After the FDA approval of The Amplatzer Piccolo Occluder in premature infants ≥700 g, it has been widely used as a good alternative to surgery in premature PDA that does not respond to conservative and medical treatments (13,14).…”
Section: Introductionmentioning
confidence: 99%